Literatur Review: Working memory dan Kesulitan Belajar Matematika - Asfari, Nur Amin Barokah; Rahmi, Yaumul (Universitas Negeri Malang, 2022)
Abstract: Math is still considered a difficult subject, especially in Indonesia, whether at the elementary, junior, or senior high school level. Even though in Indonesia, mathematics is one of the compulsory subjects at each level of education. Difficulties in learning mathematics cause obstacles in the mathematics learning process. Students who experience obstacles in mastering one mathematical concept will tend to experience difficulties in subsequent concepts. Like a snowball, if the concept cannot be mastered, students will have difficulty in understanding the next concept. As a result, more and more concepts will not be achieved. One factor that is considered to be related to learning difficulties in mathematics is working memory. This study aims to examine the role of working memory in students' math difficulties. The method used in this study is a literature review of various references and research journals. As a result, working memory has a role in students' math learning difficulties. Age differences affect the role of the contribution of the working memory component in these math learning difficulties. Keywords: working memory, math difficulties Abstrak: Matematika masih dianggap sebagai pelajaran yang sulit, khususnya di Indonesia, baik di tingkat SD, SMP, atau SMA. Padahal di Indonesia, matematika menjadi salah satu mata pelajaran wajib di setiap jenjang pendidikan tersebut. Kesulitan dalam belajar matematika menimbulkan hambatan dalam proses pembelajaran matematika. Siswa yang mengalami hambatan dalam menguasai satu konsep matematika akan cenderung mengalami kesulitan pada konsep-konsep selanjutnya. Ibarat bola salju, apabila konsep tersebut belum bisa dikuasai, siswa akan mengalami kesulitan dalam memahami konsep berikutnya. Akibatnya, akan semakin banyak konsep yang tidak akan bisa dicapai. Salah satu faktor yang dianggap berkaitan dengan kesulitan belajar matematika adalah working memory. Kajian ini bertujuan untuk mengkaji peran working memory dalam kesulitan matematika (math difficulties) pada siswa. Metode yang digunakan dalam kajian ini adalah literatur review dari berbagai referensi dan jurnal penelitian. Hasilnya, working memory memiliki peran dalam kesulitan belajar matematika pada siswa. Perbedaan usia mempengaruhi peran kontribusi komponen working memory pada kesulitan belajar matematika ini. Kata kunci: working memory, kesulitan belajar matematika